Status Gizi, Perilaku Merokok di Dalam Rumah dengan Kejadian Pneumonia - Siti Rafidah Yunus; Maria Ekawati; Pritha Maya Savitri (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2020)
Introduction: The doctor-patient relationship is based on good quality of communication and interaction with thepatient, so that it not only can help speed up the healing process, but also make the patient feel comfortable sincethe first visit to the health service. When dealing with pediatric patients, the ability to build a relationship of mutualtrust is done with a more open, honest attitude and understanding what they are feeling. Aim of study: This studyaims to see a real picture of the relationships, interactions and interpersonal communication between doctors andpatients in health care. Method: This study uses a qualitative descriptive study where data is obtained throughinterview transcripts, field observation data notes and photo documentation. A total of 7 participants were obtainedthrough a purposive sampling technique on pediatricians who are accustomed to engaging in effective relationships,interactions and communication with pediatric patients, families and introductors. Data were then analyzed usingthe Miles and Huberman method. Results and Discussions: The results of this study indicate 66.67% of parents orfamily members have smoking habits around children and 66.67% smoke when gathering with family. Most parentsor family members have the habit of opening windows as much as 75.76% of people. The results of bivariateanalysis showed that there was no relationship between nutritional status and the incidence of unde r-fivepneumonia (p = 0.732) and there was a relationship between smoking behavior and under-five pneumonia events (p= 0.021). Besides, smoking behavior at home can increase the incidence of pneumonia in toddlers. Conclusions:Therefore it is necessary to increase family awareness so as not to smoke near children.